Adhesion plaques of Rous sarcoma virus-transformed cells contain the src gene product. - Rohrschneider, L R (1980)
Another intracellular location of the Rous sarcoma virus (RSU) src gene product (pp60src) has been detected within RSV-transformed cells by indirect immunofluorescence. By using rabbit anti-tumor serum specific for pp60src, a speckled pattern of fluorescence was found on the ventral surface of RSV (Schmidt-Ruppin strain)-transformed normal rat kidney cells. Several tests indicated that this pattern was specific for pp60src. In addition, interference-reflection microscopy was used to visualize cellular adhesion plaques, which are the points at which cells attach to the substratum. Simultaneous immunofluorescence and interference-reflection microscopy indicated that the speckles of pp60src fluorescence corresponded exactly to the adhesion plaque structures. The presence of pp60src within the adhsion plaques was further demonstrated by indirect immunofluorescences on isolated adhesion plaques that remained bound to glass after removal of the cells. pp60src also was observed in adhesion plaques of RSV-tranformed chicken embryo fibroblasts (CEF) and mouse fibroblasts, as well as CEF infected with the temperature-sensitive RSV mutant tsNY68 and grown at permissive temperature. At nonpermissive temperature, pp60src was not detectable in adhesion plaques of the tsNY68-infected CEF. Adhesion plaques serve as focal points of microfilament bundle attachment, and thse results suggest that pp60src interacts directly with cellular cytoskeletal components.